Innovations and Archaic Elements in Consciousness - Savčiukas, Valerijus (Problemos, 1990)
The author substantiates the difference between the couple of categorical concepts "innovations - traditions" and that of "innovations - archaic elements in consciousness" and refutes the identification of the archaic elements in consciousness with the alienated and transformed forms of consciousness.